PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TEKNIK NUMBERED HEADS TOGETHER (NHT) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI SMKN 4 PADANG - Wahyuna, Junia; Zuzano, Fazri; Harisman, Yulyanti (Pendidikan Matematika, 2013)
The research is motivated by reality in the school that the students did not have responsibility in group discussion and studentsâ understanding of mathematical concept that still low. To solve this problem the researcher do the research by applying cooperative learning technique Number Heads TogetherÂ  (NHT). This research is to determine whether studentsâ understanding of concepts mathematical by using cooperative learning technique Number Heads Together (NHT) better than studentsâ understanding of mathematical concepts by using conventional strategy. Type of this research was experiment with research design randomly through subject. Post-test was as instrumentation in this research. Data analysis was done by using hypothesis testing one way. Number Heads Together (NHT) technique is to guide the students to share the ideas and knowledge to achieve the goal of learning. In learning process, this technique also help the students to improve their responsibility. If the studentsâ responsibility in learning had been appeared, it means the studentsâ understanding of mathematical concept also improve. The result of hypothesis testing got P-value was small thanÂ Â Â Â Â Â Â Â Â Â Â  Â  , 0.002<0.05 so hypothesis was accepted. So, we can conclude that studentsâ understanding of mathematical concepts that used cooperative learning technique Number Heads Together (NHT) better than conventional strategy at XI SMKN 4 Padang in academic year 2013/2014.